(untitled) (Journal of Geography and Environmental Management, 2018)
In this paper author focus attention of issues on development of high-tech innovation sector of economy in the Rudnyi Altay area. Author analyzes the impact of industrial innovating development on environmental problems. Author also provide analyze of environmental regulation for creating of positive effect for both the industrial innovating development and the environment.